Patterns of admitted cases to Respiratory Intensive Care Unit at Zagazig University Hospitals, Egypt - Adel Hassan A. Ghoneim; Rabie M. Hussein; Reda El-Ghamry; Lamiaa Y. Mahmoud (Egyptian Journal of Chest Disease and Tuberculosis, 2013)
Background: It is well accepted that early appropriate referral of patients to an ICU can significantly reduce early and possibly late mortality in the critically ill. At the same time improper selection of patients for ICU, often limits bed availability in ICUs. This in turn, adversely affects the dynamics of the whole hospital. Objective: To determine the admission pattern and outcome of patients in the Respiratory Intensive Care Unit (RICU) of Zagazig University Hospitals, Egypt. Design: The study was carried out as a prospective analytical study. Patients and methods: All cases admitted to RICU during the period from March 2010 to October 2010. They were 200 cases {126 males (63%) and 74 females (37%)} with an age range from 11 to 86 years. They were classified according to the causes of admission to RICU into 162 cases due to primary respiratory causes (81%) and 38 cases due to secondary respiratory causes (19%). On admission the following were carried out for all patients: full medical history, chest examination, assessment of Glasgow Coma Scale (GCS) and Acute Physiology and Chronic Health Evaluation II (APHCHE II) score, arterial blood gases analysis, plain chest and heart X-ray, computerized tomography (CT) electrocardiography (ECG) or echocardiography (ECHO) study when needed and assessment of the outcome. Results: Two hundred cases were admitted during the study period: 57% were referred by chest physicians, 14.5% from other hospitals, 13.5% from other departments and others from chest ward and emergency room (ER). The mean GCS and APHACHE II score were 12.7 ± 3.97 and 14.4 ± 6.5 respectively. The length of stay in RICU was 7.2 ± 7.4 days. Analysis of outcome of the cases showed that 70 patients (35%) were transferred to chest ward, 61patients (30.5%) died and 54 patients (27.0%) were discharged to home. There was a significant difference between cases with primary (1ry) and secondary (2ry) respiratory causes regarding outcome (P < 0.005) with mortality rate (26.6%) among cases with 1ry respiratory causes while in cases with 2ry respiratory causes were 60.4%. Outcome as regards source of admission showed that the highest percentage of death occurred among cases referred from chest ward and non chest physicians (63.7% and 62.5%) respectively. There was a significant association between outcome and duration of stay (P < 0.001). Concerning the outcome on using mechanical ventilation, the mortality rate in mechanically ventilated patients was 52.05% while in non mechanically ventilated patients it was 47.5%. Conclusion: This study showed that the best prognosis of admitted patients to RICU was for those who were transferred earlier especially those transferred by chest physicians and patients with 1ry respiratory diseases than those with 2ry respiratory diseases. Also, cases with high Glasgow Coma Scale and low APACH II score and those with a short duration of stay in RICU, especially without the need for mechanical ventilation had a good prognosis. Therefore, considering those aspects in the clinical practice would be reflected as a better outcome on dealing with RICU patients.